(untitled) (Homoeopathy for All, 2023)
Eye flu, medically known as conjunctivitis, is a common eye condition that affects people of all ages. It is characterized by inflammation of the conjunctiva, the thin, transparent layer covering the white part of the eyes and the inner surface of the eyelids. Understanding the eye flu causes is crucial in preventing its spread and ensuring timely treatment. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management for conjunctivitis.